Tafsir tematik: istilah Al-Fulk dalam Al-Quran / Siti Aisyah Yusof ... [et al.] - Yusof, Siti Aisyah; Mohamad Akhir, Noor Syahidah; Mohd Taher, Muhammad Saiful Islami; Mohd Yusof, Azrul Shahimy (Universiti Teknologi MARA, Kedah, 2021)
This article discusses the terminology 'vessel' or Al-Fulk in on the Quran. Al-Fulk is one of the terminologies mentioned in the Qur'an for marine vehicles for human use in various functions, aside from the term al-Safinah and al-Jawar. This writing focuses only on the term Al-Fulk because it is mentioned more frequently in the Qur'an than al-Safinah and al-Jawar. This study is a qualitative study by means of content analysis in a thematic interpretation or tafsir mawdhu'i by reference to authoritative sources of the Qur'an, especially the books of tafsir (interpretation) and the opinion of the scholars in explaining the term Al-Fulk. The findings of this study show that the term Al-Fulk refers to the vessels used to accommodate humans, animals and goods. The term Al-Fulk also symbolizes the power of Allah SWT, the call to thank Him, and as a mean of transport for seeking livelihood.